ЕВОЛЮЦІЯ ТА ІННОВАЦІЇ В УПРАВЛІННІ ОРГАНІЗАЦІЄЮ В ЦИФРОВУ ЕПОХУ - Kaschuck, Kateryna (Zhytomyr Ivan Franko State University, 2023)
Rapidly changing conditions of business functioning, caused by global changes in geopolitics, economy, acceleration of the pace of development of digital technologies, require greater adaptability, flexibility and speed of response from the organization's management. In this connection, the concept of management 4.0 is formed and developed, which combines advanced strategies, innovative approaches and the use of modern information and communication technologies. The research is aimed at revealing the essence of this concept in the form of an analysis of the evolution of management systems and modern challenges, as well as at the development of effective strategies and tools for successful modern management, which ensures the competitiveness and stability of the enterprise on the market. In the course of the study, types of organization management were identified, including scientific, administrative, strategic, innovative management, and quality management. The article substantiates the need for improving approaches to administration in the organization, introducing innovations and advanced digital technologies into the enterprise's activities. The concept was formed and the key components of management 4.0 were determined, taking into account the modern realities and needs of Ukrainian business. Challenges faced by domestic companies are highlighted; strategies, approaches and practical recommendations for overcoming them are presented. It is proven that the application of the process approach in management contributes to the realization of internal reserves of growth and development of the enterprise, simplification of the organizational structure of subordination. And if earlier its implementation was associated with radical changes in the company, now evolutionary methods of its implementation are being actively developed. The process approach to management is aimed at reducing the company's costs, which has a positive effect on the company's profit, and therefore on financial opportunities for the implementation of innovative projects.